UNDERWATER IMAGE DEHAZING USING ENHANCED WCID - Prachi S. Shete; Nagaraj V. Dharwadkar (International Journal of Innovations in Engineering Research and Technology, 2021)
Underwater Imaging is important for research area andtechnology in ocean engineering. Underwater haze removal techniques become very important due to the use of no. of vision underwater applications. Within the recent past year, scientists are very keen to explore the mysterious underwater world. Haze brings trouble to many computer vision/graphics applications as it degrades the visibility of the scene. Haze is formed due to the attenuation and the air light. Attenuation reduces the contrast and air light increases the whiteness in the scene. This paper deals with an approach to enhanceunderwater images. The input underwater video is taken from YouTube. The proposed approach gives better result of clarity of underwater image which is veryimportant for underwater analysis